Bad girls - Wilson, Jacqueline; Sharratt, Nick (London : Corgi Yearling, 2006)
Ten-year-old Mandy must endure torment from three nasty bullies in school, but she finds solace in a new friendship with an older girl.
"First published in Great Britain by Doubleday ... 1996"--T.p. verso.
Book Links (A.L.A.), February 2002.
Booklist, January 2001.
Bulletin (Center for Children's books), March 2001.
Kirkus Review, December 2000.
Library Talk, November 2001.
Keywords: Bullies -- Fiction; Friendship -- Fiction; School stories; England -- Fiction